Integrated generation of induced pluripotent stem cells in a low-cost device. (January 2019) - Lin, Haishuang; Li, Qiang; Du, Qian; Wang, Ou; Wang, Zhanqi; Akert, Leonard; Carlson, Mark A.; Zhang, Chi; Subramanian, Anuradha; Zhang, Chi; Lunning, Matthew; Li, Ming; et al.
Abstract: Human induced pluripotent stem cells (iPSCs) have unlimited proliferation capability and potential to differentiate into all somatic cells. Their derivatives contain patients' genetic information and can model many diseases. Additionally, derivatives of patient-specific iPSCs induce minimal immune rejection in vivo . With this unique combination of properties, iPSCs open the avenue to personalized medicine including personalized drug screening, toxicity test, cell therapy and tissue engineering. However, the further advance of iPSC-based personalized medicine is currently limited by the difficulty to generate iPSCs for large populations and at affordable cost. We here report a low-cost device to address this challenge. The device allows the entire bioprocess for generating high quality and quantity of iPSCs for one patient to be done automatically within a closed conical tube without cell passaging. Additionally, iPSCs can be further differentiated into somatic cells in the device. Thus, the device also allows integrated iPSCs generation, expansion and differentiation to produce any somatic cell types. This device can be made in large quantities at low cost for manufacturing iPSCs (and their derivatives in necessary) for large populations at affordable cost. It will significantly advance the iPSCs-based personalized medicine. Graphical abstract: Reprograming fibroblasts into iPSCs is done in alginate hydrogel microtubes. The microenvironment in the tube enhances the reprograming and expansion of the generated iPSCs, while inhibits the expansion of fibroblasts, resulting in high purity and yield of iPSCs. Highlights: iPSCs are generated in alginate hydrogel tubes (AlgTubes). AlgTubes create a microenvironment that generates iPSCs at high purity and yield. AlgTubes are used to build a small low-cost Single-Conical-Tube (SCOT) device. Generating iPSCs for a patient can be automatically done in a SCOT device.